Pentecostalism and the Promotion of Human Capital in Ghana - Okyerefo, M.P.K. (Trinity Journal of Church and Theology 2(XVII): 54-68, 2009)
Religious ideas and actors are contributing to development in contemporary Africa. This paper explores how Pentecostalism in Ghana foments ideals and networks that transform individuals and groups into the kind of human capital necessary for development. Rather than argue for a unique religious answer to development, since no contemporary development theory has such a unique solution, the paper argues that religion promotes a sense of community and belonging that foments development. A community is made up of individuals. Building up the potentials of the individuals and networking them for the purpose promotes development. Development requires both material and non-material human needs. Just as food security and shelter are basic necessities of life in the process of development, so is a sense of human community and belongingness. Material needs do advance religion as seen in faith gospel theology. So too does a community of believers forge networks that build human capital as the case of Pentecostalists in Ghana depicts.